Suppressing grain growth on Cu foil using graphene - Lee, Jaeyeong; Shin, Hojun; Choi, Jae Young; Yu, Hak Ki (Coatings, 2018)
The effect of graphene coating on the growth of grains on bulk copper film was studied. When methane gas is catalytically decomposed on the surface of copper, and a carbon-copper solid solution is formed at high temperature, precipitated carbon on the copper surface forms graphene during rapid cooling through strong sp2 covalent bonding. The graphene layer can prevent the growth of grains by suppressing the diffusion of copper atoms on the surface, even after continuous heat treatment at high temperatures. The actual size of the copper grains was analyzed in terms of repetitive high-temperature heat treatment processes, and the grain growth process was simulated by using thermodynamic data, such as surface migration energy and the binding energy between copper and carbon. In general, transition metals can induce graphene growth on surfaces because they easily form carbon solid solutions at high temperatures. It is expected that the process of graphene growth will be able to suppress grain growth in transition metals used at high temperatures and could be applied to materials that are prone to thermal fatigue issues such as creep.
Keywords: Cu-C binding energy; Grain growth; Graphene; Pseudo-free-standing